THE ROLE OF MOTIVATION IN LEARNING - Xasanov , Muzaffar Yorqin o‘g‘li (Educational Research in Universal Sciences, 2023)
This article will discuss about the role motivation in teaching and learning new language. Theoretical and methodological aspects of motivation in teaching and studying will be provided.